2014
DOI: 10.1007/s00418-014-1287-x
|View full text |Cite
|
Sign up to set email alerts
|

Presence of lymphatics in a rat tendon lesion model

Abstract: Tendons lack sufficient blood supply and represent a bradytroph tissue with prolonged healing time under pathological conditions. While the role of lymphatics in wound/defect healing in tissues with regular blood supply is well investigated, its involvement in tendon defects is not clear. We here try to identify the role of the lymphatic system in a tendon lesion model with morphological methods. A rat Achilles tendon lesion model (n = 5) was created via surgical intervention. Two weeks after surgery, animals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…In this sense, it has to be mentioned that CD31 is not exclusively expressed in vascular endothelium, but also in lymphatic endothelium, 23,52-55 but because the here observed iris vessels were lacking PROX1þ nuclei, these were therefore considered vascular capillaries. Additionally, in none of our samples investigated, a typical arrangement of endothelial nuclei resulting in a pearl string-like pattern of PROX1-positivity 55 was obvious. While VEGFR3-imunoreactivity was observed in CD68þ macrophages 51 it is most likely that VEGFR3 þ/ PROX1À/CCL21À cells in the iris and also the VEGFR3-positive cells of similar size and shape in the ciliary body represent macrophages.…”
Section: Discussionmentioning
confidence: 67%
“…In this sense, it has to be mentioned that CD31 is not exclusively expressed in vascular endothelium, but also in lymphatic endothelium, 23,52-55 but because the here observed iris vessels were lacking PROX1þ nuclei, these were therefore considered vascular capillaries. Additionally, in none of our samples investigated, a typical arrangement of endothelial nuclei resulting in a pearl string-like pattern of PROX1-positivity 55 was obvious. While VEGFR3-imunoreactivity was observed in CD68þ macrophages 51 it is most likely that VEGFR3 þ/ PROX1À/CCL21À cells in the iris and also the VEGFR3-positive cells of similar size and shape in the ciliary body represent macrophages.…”
Section: Discussionmentioning
confidence: 67%
“…These observations agree well with previous x-ray dispersive studies, where a gradient was demonstrated from epidermis to subcutis in human 29 and in guinea by guest on May 12, 2018 http://hyper.ahajournals.org/ Downloaded from pig skin. 30 In line with these observations, by application of 7T 23 Na + magnetic resonance imaging, it was shown that there was a substantial accumulation of Na + in or directly under epidermis. 31 Interestingly, this Na + accumulation was not associated with a significant volume increase in the same area as would have been expected if the Na + exerted at least some of its crystalloid osmotic effect.…”
Section: Osmolyte and Electrolyte Gradients In Skin And Implications mentioning
confidence: 74%
“…Because the other major component of the tail, tendon, does not contain lymphatics, 23 the harvested tail lymph will be representative for skin. Moreover, tail skin accumulated salt to a similar extent as back skin and should therefore be representative for skin in general.…”
Section: Evaluation Of Methods and Limitationsmentioning
confidence: 99%
“…4 . For descriptive histology 7 µm thick cryosections were stained either using Hematoxylin & Eosin stain (data not shown), Masson-Goldner’s trichrome stain or Herovici’s polychrome stain according to the manufacturer’s guidelines (see SI methods for further details).…”
Section: Methodsmentioning
confidence: 99%